Intrasession Repeatability and Intersession Reproducibility of Macular Vessel Parameters on Optical Coherence Tomography Angiography in Glaucomatous and Non-Glaucomatous Eyes. (3rd July 2022) - Vorperian, Alexander; Khan, Nasir; Lee, Jae; Burkemper, Bruce; Zhou, Xiao; Grisafe, Dominic; LeTran, Vivian; Chu, Zhongdi; Wong, Brandon; Xu, Benjamin; Song, Brian; Wang, Ruikang K.; et al.
Abstract: Purpose: Using optical coherence tomography angiography (OCTA), this study compared intrasession repeatability versus intersession reproducibility of macular vessel parameters in glaucoma and non-glaucoma subjects. Methods: 6 × 6 mm 2 macular OCTA scans (Cirrus HD-OCT 5000) were acquired from glaucomatous and non-glaucomatous subjects as part of an observational, longitudinal study. Vessel area density (VAD) and vessel skeleton density (VSD) were calculated using research-based quantification software while perfusion density (PDZ ) and vessel density (VDZ ) were calculated using commercially developed software (Cirrus 11.0, Carl Zeiss Meditec). Intrasession repeatability and intersession reproducibility were determined using within-eye standard deviation (SW ), within-eye coefficient of repeatability (CRW ), within-eye coefficient of variation (CVW ), and intraclass correlation coefficients (ICC). Results: The intrasession repeatability and intersession reproducibility for macular OCTA parameters were similar to one another for both non-glaucomatous and glaucomatous eyes. Intrasession CVW from the non-glaucoma group ( n  = 73) was 1.097% for VAD, 1.007% for VSD, 2.980% for PDZ, and 2.714% for VDZ. Intersession CVW from the non-glaucoma group ( n  = 55) was 1.389% for VAD, 1.279% for VSD, 2.935% for PDZ, and 2.695% for VDZ . Intrasession CVW from the glaucoma group ( n  = 59) was 1.189% for VAD, 0.970% for VSD, 3.827% for PDZ, and 3.542% for VDZ . Intersession CVW from the glaucoma group ( n  = 45) was 1.412% for VAD, 1.132% for VSD, 3.915% for PDZ, and 3.654% for VDZ . Non-glaucomatous intrasession ICC ranged from 0.711 to 0.824, non-glaucomatous intersession ICC ranged from 0.649 to 0.762, glaucomatous intrasession ICC ranged from 0.710 to 0.853, and glaucomatous intersession ICC ranged from 0.661 to 0.827. Conclusions: Macular OCTA scans can be a useful tool in monitoring the longitudinal progression of glaucoma due to their high repeatability and reproducibility.